PMA1-containing extracellular vesicles of Candida albicans triggers immune responses and colitis progression - Zhen Xu; Shuping Qiao; Zelin Wang; Chen Peng; Yayi Hou; Baorui Liu; Guochun Cao; Tingting Wang (Gut Microbes)
Candida albicans (C. albicans) exhibits aberrant changes in patients with colitis, and it has been reported to dominate the colonic mucosal immune response. Here, we found that PMA1 expression was significantly increased in C. albicans from patients with IBD compared to that in healthy controls. A Crispr-Cas9-based fungal strain editing system was then used to knock out PMA1 expression in C. albicans. Compared to WT-C.a, ΔPMA1-C.a could not aggravate colitis. Proteomic analysis showed that PMA1 was transported by extracellular vesicles (EVs) of C. albicans. PMA1-containing EVs aggravated colitis, modulated the migration of cDC2 from the lamina propria to mesenteric lymph nodes, and induced TH17 cell differentiation. Moreover, the adaptor protein CARD9 was critical in PMA1-containing EV-induced colitis, and CARD9-deficient DCs did not induce TH17 cell differentiation or IL-17A production. Mechanically, CARD9 combines with the glycolytic protein GAPDH (aa2–146 domain) through its CARD region. CARD9 deficiency led to decreased enzyme activity of GAPDH and decreased glycolysis of DCs. These findings indicate that PMA1 is a potential virulence factor responsible for the pathogenesis of C. albicans colitis.